O dilema identitário dos agentes de segurança penitenciária: guardiões ou policiais? - Victor Neiva e Oliveira (2018)
This thesis had as main objective to analyze the process of construction of the professional identity of the prison officers of Minas Gerais. The penitentiary system has undergone drastic changes in the last twenty years and has demanded a specific profile of individuals to compose its staff. In the course of these years, there has been a strong investment in training programs aimed making prison officers more repressive, strategic and efficient in maintaining security and order in prisons. This professionalization, in turn, occurred through the progressive incorporation of organizational elements characteristic of the military police forces to the custodial work and valorization of the military performance. The identification with the military field generated an identity dilemma in the occupational group: guardians or cops?. Some prison officers have rejected the image of the guardian and have been recognized as like police involved in crimefighting operations inside and outside the prisons. A dual professional identity, custodial and police officer, has been established with deep repercussions in prison environments and in the way the order has been built within